Service Quality Research to Increase Customer Satisfaction at Yamaha 71 Motor Pamulang Workshop - Bayu Lhutfi R; Erika; Iqbal Dzulfukor (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this research is to analyze the quality of service to increase customer satisfaction at the automotive repair shop